Damage propagation and failure mechanism of single dome historical Masonry Mosque after February 6, 2023, Kahramanmaras,earthquake doublets (Mw = 7.7 and Mw = 7.6) - Onat, Onur; Ozmen, Alper; Ozdemir, Engin; Sayin, Erkut (Elsevier Science Inc, 2024)
Many historical masonry mosques and minarets, including Milky Minaret Mosque and Ulu Mosque, which are very close to Ak Minaret Mosque in Malatya, suffered severe damage and collapsed after the Kahramanmaras, , earthquake on February 6, 2023. Despite the settled loose soil properties and the presence of a small stream flow near the mosque, Ak Minaret Mosque, a historical masonry mosque with a single dome and square, remains operational even after the aforementioned earthquakes. Additionally, DEMA's strong ground motion station was out of service during both earthquakes. This situation raises questions about the mosque's ability to withstand the seismic load. The basic purpose of this paper is to investigate in detail the seismic performance, damage limits, the reason for unexpectedly less damage due to the earthquakes, the potential failure mode, and possible resisted earthquake loads of the historical Ak Minaret Mosque in Malatya, T & uuml;rkiye. To achieve this goal, first, dynamic identification was performed on the mosque one year prior to the aforementioned earthquakes. Next, the material properties were determined using both non-destructive and destructive testing methods. Following the dynamic identification, a numerical model was generated by 3-D solid elements, and this 3-D model was calibrated using the dynamic identification tests. The mosque underwent both nonlinear static and nonlinear dynamic analyses. Nine seismic records were selected for the nonlinear dynamic analysis. Five of them were national, including even Kahramanmaras, , earthquake records, and three of them were selected from an international database on the basis of fault characteristics and site classification. The analysis results indicate that Ak Minaret Mosque incurred less damage than expected during the Kahramanmaras, , earthquakes. This could be due to soil improvement prior to the construction of Ak Minaret Mosque in 1573. Moreover, the effective restoration increased stiffness and maintained the mosque's stability. Finally, the possible resisted PGA by the mosque was around 0.22 g.
Keywords: Ak Minaret Mosque; February 6, 2023, earthquakes; Nonlinear static and dynamic analysis; Malatya; Failure of single dome mosque